KURIKULUM MERDEKA MADRASAH DALAM PANDANGAN FILSAFAT PENDIDIKAN HUMANISME - Hamdani Hamdani; Wedra Aprison (CV. ADIBA AISHA AMIRA, 2024)
The Merdeka Curriculum in Madrasas, when viewed from the perspective of the Humanist Education philosophy, emphasizes developing the unique potential of each student. This research aims to explore the views of humanist educational philosophy on the Independent Curriculum. This research uses descriptive analysis methods with library research and observations at MTs Rambatan, Tanah Datar Regency. The implications of this research can guide the view of humanist educational philosophy towards the implementation of the independent curriculum in Madrasas. The Humanism Education Philosophy focuses on human values, freedom and individual equality. In the context of the Independent Curriculum, this approach leads to giving Madrasahs the freedom to adapt the curriculum to pay more attention to students' individual needs, allowing them to explore their interests, talents and needs in more depth. Teachers in Madrasas become facilitators who support the holistic development process of students, both in terms of academics and moral values. Apart from that, this approach also encourages inclusivity and tolerance, respects differences and strengthens the values of mutual respect for cultural diversity and beliefs in the Madrasa educational environment. Thus, the Merdeka Curriculum in Madrasas, seen from the perspective of the Humanist Education philosophy, emphasizes individual empowerment, the development of human values, and inclusive and in-depth learning for each student.